Serum alpha-tocopherol, retinol and neopterin during paclitaxel/carboplatin chemotherapy - Melichar, Bohuslav; Kalábová, Hana; Krčmová Kujovská, Lenka; Urbánek, Lubor; Hyšpler, Radomír; Malířová, Eva; Solichová, Dagmar (Anticancer research, 2007)
BACKGROUND: Disorders of antioxidant balance are considered to be involved in the toxicity associated with radiotherapy or chemotherapy. PATIENTS AND METHODS: Serum alpha-tocopherol and retinol were determined, by high performance liquid chromatography, before and during therapy with a combination of paclitaxel and carboplatin in 28 patients with breast and ovarian cancer. Serum neopterin and cholesterol were measured using a radioimmunoassay and enzymatic colorimetric method, respectively. RESULTS: Compared to pretreatment concentrations, a significant increase was observed in serum alpha-tocopherol and retinol concentrations during therapy that was associated with decreased serum neopterin concentrations. Serum alpha-tocopherol concentrations were significantly higher during therapy in patients who did not experience serious toxicity. CONCLUSION: An increase in alpha-tocopherol and retinol during therapy with combination paclitaxel/carboplatin may be explained by inhibition of systemic immune activation secondary to control of the tumor with effective chemotherapy. Lower alpha-tocopherol concentrations were associated with the toxicity of therapy.
Keywords: Neopterin; Vitamin A; neopterin; Antineoplastic Combined Chemotherapy Protocols; alpha-Tocopherol; Ovarian Neoplasms; vitamin A; vysokoúčinná kapalinová chromatografie; Carboplatin; Adult; Aged; alfa-tokoferol; dospělí; nádory prsu; senioři; paclitaxel; karboplatina; nádory vaječníků; Paclitaxel; Chromatography, High Pressure Liquid; lidé; ženské pohlaví; Breast Neoplasms; Humans; protokoly protinádorové kombinované chemoterapie; Financing, Organized; Female; financování organizované; lidé středního věku; Middle Aged